SINTESIS DAN AKTIVITAS ANTIOKSIDAN SENYAWA 2-METOKSI- 4,6-DI(PROP-1-ENIL) FENOL DARI EUGENOL - , Hernawan, Drs. Bambang Purwono, M.Sc, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Synthesis and antioxidant activity of 2-methoxy-4,6-di(prop-1-enyl) phenol from eugenol have been investigated. Synthesis was conducted via three stages of reaction. The first step reaction was CTAB micellar catalytic O-allylation reaction at room temperature to give 4-allyl-1-(allyloxy)-2-methoxybenzene (2). Compound (2) was subsequently heated under Claisen rearrangement to produce 2,4-diallyl-6-methoxyphenol (3). The last step was isomerization of compound (3) in alkaline conditions in ethylene glycol to yield 2-methoxy-4,6-di(prop-1-enyl) phenol (4). Antioxidant activity test was conducted by TBARS and DPPH methods. TBARS test showed that the compound (4) at 50 Î¼M could inhibit the oxidation of linoleic acid indicated by the increasing of time lag phase (96 + 2.94 minutes), reducing the rate of propagation (+ 54.54%) and reducing of malonal dialdehide (MDA) formation (68.04 + 0.84%). In addition, DPPH test revealed that compound (4) has an activity as anti-DPPH with IC50 101.23 Î¼M comparable with BHT IC5098.98 Î¼M.